Isolated rupture of the corpus spongiosum with urethral injury diagnosed by pre‐surgical MRI. Issue 1 (22nd November 2022) - Yokoyama, Shuhei; Tsuboi, Ichiro; Ogawa, Kohei; Yoshioka, Saori; Kobayasi, Yusuke; Nakajima, Hirochika; Nagami, Taichi; Yamasaki, Seigen; Wada, Koichiro
Abstract : Introduction: Penile fracture is typically defined as the rupture of the corpus cavernosum. Case presentation: A 61‐year‐old man presented with swelling, pain, and bruising of his penis, along with gross hematuria. He reported that he sustained this injury while having sex with his wife. We suspected a penile fracture and obtained magnetic resonance imaging, which showed a rupture of the ventral corpus spongiosum and clarified the appropriate approach for repair. We used a direct transverse incision to repair both the urethral injury and the corpus spongiosum. Surgery went well, without any significant intraoperative or postoperative complications. We removed the urinary catheter on postoperative day 8, and cystoscopy showed no urethral stenosis on postoperative day 17. The patient's postoperative erectile function was the same as before his injury. Conclusion: Magnetic resonance imaging was useful for detect the site of rupture. Ventral direct transverce incision made him a good clinical course.